Substâncias antifúngicas de Xylaria sp., um fungo endofítico isolado de Palicourea marcgravii (Rubiaceae) - Cafêu, Mariana Carrara [UNESP] (2005)
Five compounds, 2-hexyl-3-methyl-butanodioic acid (1), cytochalasin D (2), 7-dechlorogriseofulvin (3), cytochalasin B (4) and griseofulvin (5), have been isolated from the endophytic fungus Xylaria sp., and their structures were elucidated on the basis of spectroscopic data. In the bioautography assay against Cladosporium cladosporioides and Cladosporium sphaerospermum, compounds 1 and 2 were found to be active while compounds 3, 4 and 5 did not show antifungal activity.